2019
DOI: 10.1007/s10157-019-01802-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of dotinurad, a novel selective urate reabsorption inhibitor, in Japanese hyperuricemic patients with or without gout: an exploratory, randomized, multicenter, double-blind, placebo-controlled, parallel-group early phase 2 study

Abstract: Background Dotinurad, a novel selective urate reabsorption inhibitor (SURI) that has a future potential for the treatment of hyperuricemia, reduces serum uric acid levels by selectively inhibiting urate transporter 1 (URAT1). We evaluated the efficacy and safety of dotinurad in hyperuricemic Japanese patients with or without gout. Methods The study design was an exploratory, early phase 2 study that ran for 8 weeks. It was a randomized, multicenter, double-blind, placebo-controlled, parallel-group study, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…After removing duplicates and screening titles and abstracts, 30 full-text articles were reviewed. Finally, four RCTs (684 patients) were eligible for inclusion in the study (Figure 1) [2,7,8,10]. All the included studies assessed the efficacy and safety of dotinurad in hyperuricemic patients with or without gout.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After removing duplicates and screening titles and abstracts, 30 full-text articles were reviewed. Finally, four RCTs (684 patients) were eligible for inclusion in the study (Figure 1) [2,7,8,10]. All the included studies assessed the efficacy and safety of dotinurad in hyperuricemic patients with or without gout.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperuricemia, defined as a serum uric acid level > 7 mg/dl, is associated with an increased risk of urate deposition diseases, namely gout, uric acid nephrolithiasis, and urate neuropathy [1]. Additionally, an increased prevalence of chronic kidney disease (CKD), diabetes mellitus (DM), and hypertension (HTN) exist in patients with increased serum uric acid levels [2]. The global burden of hyperuricemia and gout is rising, projecting that gout mortality may increase by 55% in 2060 [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Completed phase 2 studies of dotinurad demonstrated a potent uric acid lowering effect as well as a favorable safety profile [10,11]. In a phase 1 study in healthy adults, PK parameters of dotinurad showed a linear C max and its time to C max (T max ) and elimination half-life (T 1/2 ) were approximately 3 and 10 h, respectively, which were nearly constant irrespective of the dose level.…”
Section: Introductionmentioning
confidence: 99%